The Determinants of Mutual Fund Performance: A Cross-Country Study - Ferreira, Miguel A.; Keswani, Aneel; Miguel, António F.; Ramos, Sofia B. (Review of Finance, 2013)
Abstract We use a new data set to study the determinants of the performance of open–end actively managed equity mutual funds in 27 countries. We find that mutual funds underperform the market overall. The results show important differences in the determinants of fund performance in the USA and elsewhere in the world. The US evidence of diminishing returns to scale is not a universal truth as the performance of funds located outside the USA and funds that invest overseas is not negatively affected by scale. Our findings suggest that the adverse scale effects in the USA are related to liquidity constraints faced by funds that, by virtue of their style, have to invest in small and domestic stocks. Country characteristics also explain fund performance. Funds located in countries with liquid stock markets and strong legal institutions display better performance.